Fungal infections and control strategies in cultured marine finfish: a minireview - Mohammad Tamrin Mohamad Lal; Lim, Leong Seng; Lau, Lik-ming; Sai, Elden Long Chang; Asyraf Abdul Momin; Muhd Sharil Izzan Hamid (The Society for Antibacterial and Antifungal Agents, Japan, 2024)
Marine fish farming served as a sustainable alternative to capture fisheries. However, it faced challenges such as disease management, water quality maintenance, and minimizing environmental impacts. Among these challenges, fungal infections are particularly concerning. Traditionally, chemical treatments raise concerns about potential toxicity to fish and humans, environmental impact, and resistance development. In response to these issues, there is growing interest in sustainable biocontrol strategies, including the use of probiotics, phytobiotics, postbiotics, microalgae, and fungal parasites as antifungal agents. This mini-review provides a brief overview of fungal infections in marine fish and discusses current fungal biocontrol strategies in aquaculture. By adopting these sustainable control methods, the aquaculture industry can improve fish health and productivity while reducing its reliance on harmful chemicals.